ELASTISITAS PERMINTAAN JASA LOUNDRY ADI HIDAYAT DI KECAMATAN SAMBALIUNG KABUPATEN BERAU: ELASTISITAS PERMINTAAN JASA LOUNDRY ADI HIDAYAT DI KECAMATAN SAMBALIUNG KABUPATEN BERAU - Shandy Barkah (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2018)
The purpose of this research is to know the elasticity of demand for laundry service in Sambaliung District of Berau Regency whether it is elastic or inelastic, so it is useful for interested parties to take policy in the future. Based on the research result, it can be seen that the elasticity of laundry service demand in Sambaliung District of Berau Regency is elastic (É›> 1). This is shown from the average elasticity value is 3,337 means that the hypothesis expressed by the authors accepted. The calculation result from simple linear regression equation is known Y = - 47,1+11,950 X with elasticity value in year 2016 is equal to 13,349 (É›> 1) with total of Laundry Service production value is Rp. 738,062,500.